(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
In this article, the degree of harm caused by the melon fly pest to melons is studied, and it is aimed to increase the effectiveness of agrotechnical measures to achieve high efficiency in the fight against it by using chemical preparations and to save the cultivated crop.